Impact of Various Thermistors on the Properties of Resistive Microbolometers Fabricated by CMOS Process - Yaozu Guo; Haolan Ma; Jiang Lan; Yiming Liao; Xiaoli Ji (Micromachines, 2022)
Microbolometers based on the CMOS process has the important advantage of being automatically merged with circuits in the fabrication of larger arrays, but they typically suffer from low detectivity due to the difficulty in realizing high-sensitivity thermistors in the CMOS process. In this paper, two resistive microbolometers based on polysilicon and metal Al thermistors, respectively, are designed and fabricated by the standard CMOS process. Experimental results show that the detectivity of the two resistive microbolometers can reach a maximum of 1.78 × 109 cmHz1/2/W at 25 μA and a maximum of 6.2 × 108 cmHz1/2/W at 267 μA. The polysilicon microbolometer exhibits better detectivity at lower bias current due to its lower effective thermal conductivity and larger resistance. Even though the thermal time constant of the polysilicon thermistor is three times slower than that of the metal Al thermistor, the former is more suitable for designing a thermal imaging system with sensitive and low power consumption.